Analisa Praktik Jual Beli Paket Data Internet Ditinjau dari Perspektif Ekonomi Islam - Novanda Eka Nurazizah (ISLAMIC BUSINESS and FINANCE (IBF), 2020)
This study discusses how to practice the sale and purchase of active period of internet data package in Counter komplek  pasarTamansari, concerning the validity period of internet data packet prime card. The existence of incompatibility of the active period of data packet raises a problem that resulted in a loss on either party. The ative period og internet data packets does not matc what is in the product packaging.  This research used qualitative research design, conducted in actual life or reality. In this case the object of research is the Counter komplek pasar tamansari.  Concluded that the law of sale and purchase is valid, because in accordance with harmonious and conditions af sale and purchase. However, the transaction object is inconsistent with the original agreement presented by the seller. In this case, than the benefits are not fully fulfilled due to the defects of the object being traded, then the sale is broken (fasid) or canceled.